2013
DOI: 10.1007/s11606-013-2536-8
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourcing—Harnessing the Masses to Advance Health and Medicine, a Systematic Review

Abstract: OBJECTIVE:Crowdsourcing research allows investigators to engage thousands of people to provide either data or data analysis. However, prior work has not documented the use of crowdsourcing in health and medical research. We sought to systematically review the literature to describe the scope of crowdsourcing in health research and to create a taxonomy to characterize past uses of this methodology for health and medical research. DATA SOURCES: PubMed, Embase, and CINAHL through March 2013. STUDY ELIGIBILITY CRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
249
0
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 303 publications
(256 citation statements)
references
References 32 publications
1
249
0
6
Order By: Relevance
“…With regards to the demographics of the crowd, Ranard et al’s review found that few articles reported on demographics and for those that did, the level of demographics reported varied [27]. However, Khare et al state that the crowd should be poorly defined and diverse [3].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…With regards to the demographics of the crowd, Ranard et al’s review found that few articles reported on demographics and for those that did, the level of demographics reported varied [27]. However, Khare et al state that the crowd should be poorly defined and diverse [3].…”
Section: Discussionmentioning
confidence: 99%
“…In AMT and CrowdFlower, the initiator (or crowdsourcer) posts a task and the ‘crowd’ responds and are paid in small quantities for completing small HITs. Other online platforms use distributed online processes to compete for the best solution, such as InnoCentive or CrowdMed [27,32]. Advances in mHealth, such as wearable technologies and sensors, could enable real–time data collection and monitoring from mass amounts of people [38].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations